Gender Gaps in Letter-Sound Knowledge Persist Across the First School Year - Sigmundsson, Hermundur; Dybfest Eriksen, Adrian; Ofteland, Greta S.; Haga, Monika (Frontiers in Psychology, 2018)
Literacy is the cornerstone of a primary school education and enables the intellectual and social development of young children. Letter-sound knowledge has been identified as critical for developing proficiency in reading. This study explored the development of letter-sound knowledge in relation to gender during the first year of primary school. 485 Norwegian children aged 5-6 years completed assessment of letter-sound knowledge, i.e. uppercase letters- name; uppercase letter –sound; lowercase letters- name; lowercase letter-sound. The children were tested in the beginning, middle, and end of their first school year. The results revealed a clear gender difference in all four variables in favor of the girls which were relatively constant over time. Implications for understanding the role of gender and letter-sound knowledge for later reading performance are discussed